O ensino do teatro na escola pública: uma experiência inclusiva para surdos (um estudo de caso) - Sousa, Liliane Alves de (2016)
This research aims to investigate whether the differences between deaf and hearing make it difficult or impossible to them the theatrical practice in the same space, sharing experiences and theatrical codes. It refers to the theater education, deaf education and inclusion. It is based on the study of experiences lived with a group of students of the 8th year of elementary education in a public school in the city of João Pessoa, from twenty-six class time between August and November 2015. The meetings took place in the period of regular art classes and generally in the classroom. To carry out the lessons it were used theater games and playful experiences, activities of reading, writing and dialogical actions. At the end of the educational process and under the guidance of a Theatre teacher, the students collectively prepared a theatrical presentation based on an excerpt from Ariano Suassuna. The adaptation did not focus on the theatrical text, but was based on the work context, experiencing a more visual theater than verbal, in order to make clear that art, specifically the theater, needs to be accessible to all, once it is a space of visibility of what may be somehow hidden. The inclusive aspect of theater should be used more effectively now that more and more individuals are excluded, separated by the differences between them. It was observed that the theatrical practice is possible for deaf and hearing in a same group sharing experiences, using tools and other adjustments. However the tools were not used to conceal or to evidence the deafness, but to make effective the experience and manage the communication between players/actors who are either in the classroom or on stage and also between them and the public.